2003
DOI: 10.1105/tpc.009464
|View full text |Cite
|
Sign up to set email alerts
|

Leaf Mitochondria Modulate Whole Cell Redox Homeostasis, Set Antioxidant Capacity, and Determine Stress Resistance through Altered Signaling and Diurnal Regulation

Abstract: To explore the role of plant mitochondria in the regulation of cellular redox homeostasis and stress resistance, we exploited a Nicotiana sylvestris mitochondrial mutant. The cytoplasmic male-sterile mutant (CMSII) is impaired in complex I function and displays enhanced nonphosphorylating rotenone-insensitive [NAD(P)H dehydrogenases] and cyanide-insensitive (alternative oxidase) respiration. Loss of complex I function is not associated with increased oxidative stress, as shown by decreased leaf H 2 O 2 and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
382
0
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 471 publications
(407 citation statements)
references
References 75 publications
(92 reference statements)
23
382
0
2
Order By: Relevance
“…Thereby, AOX was shown to contribute to a slight (15 %) restriction of the size of necrotized viral lesions during TMV-induced HR-type cell death in tobacco (Ordog et al, 2002). Nicotiana sylvestris mitochondrial mutants with elevated levels of AOX protein and altered expression of antioxidant enzymes also display reduced number and size of lesions following TMV inoculation compared with control plants (Dutilleul et al, 2003). On the other hand, use of a TMV vector to produce extremely high levels of wild-type or mutant AOX protein in tobacco resulted in larger HR lesions than those produced by the empty TMV vector (Murphy et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Thereby, AOX was shown to contribute to a slight (15 %) restriction of the size of necrotized viral lesions during TMV-induced HR-type cell death in tobacco (Ordog et al, 2002). Nicotiana sylvestris mitochondrial mutants with elevated levels of AOX protein and altered expression of antioxidant enzymes also display reduced number and size of lesions following TMV inoculation compared with control plants (Dutilleul et al, 2003). On the other hand, use of a TMV vector to produce extremely high levels of wild-type or mutant AOX protein in tobacco resulted in larger HR lesions than those produced by the empty TMV vector (Murphy et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…1c). Interestingly, the diel pattern of daytime depletion and nocturnal accumulation of ascorbic acid in Agave contrasts markedly with that in Arabidopsis and other C 3 species 17,18 .…”
Section: Metabolicmentioning
confidence: 98%
“…1c). Interestingly, the diel pattern of daytime depletion and nocturnal accumulation of ascorbic acid in Agave contrasts markedly with that in Arabidopsis and other C 3 species 17,18 .The reprogramming of the day/night pattern of ascorbic acid turnover in Agave is intriguing if ascorbic acid is a key component of a redox hub that integrates metabolic information and environmental stimuli to tune responses within the cellular signalling network 19 . Recent studies have shown that many organisms, including Arabidopsis, have a redox rhythm that is dictated by circadian clock components and metabolic activities such as the production and scavenging of reactive oxygen species (ROS) [20][21][22] .…”
mentioning
confidence: 99%
“…In the tobacco CMSII mutant, which lacks the major mitochondrial NADH dehydrogenase (Complex I), the rate of photosynthesis is decreased, notably during dark -light transitions or when carbon fixation and photorespiration are simultaneously active (Sabar et al, 2000;Dutilleul et al, 2003a). In the same mutant, modulation of nuclear gene expression maintains whole cell redox balance (Dutilleul et al, 2003b). The analysis of the prors1 mutant of Arabidopsis, defective in an organelle-targeted tRNA synthetase, shows that nuclear photosynthetic genes are specifically down-regulated (P. Pesaresi and D. Leister, unpublished results), indicating that mitochondrion -chloroplast crosstalk might involve re-programming of the expression of nuclear chloroplast genes.…”
Section: Cross-talk Between Chloroplast and Mitochondrionmentioning
confidence: 99%